2015
DOI: 10.1017/s0950268815000734
|View full text |Cite
|
Sign up to set email alerts
|

Estimated hospitalizations attributed to norovirus and rotavirus infection in Canada, 2006–2010

Abstract: SUMMARYEnteric viruses including norovirus and rotavirus are leading causes of gastroenteritis in Canada. However, only a small number of clinical cases are actually tested for these pathogens leading to systematic underestimation of attributed hospitalizations in administrative databases. The objective of this analysis was to estimate the number of hospitalizations due to norovirus and rotavirus in Canada. Hospitalization records for acute gastroenteritis-associated discharges at all acute-care hospitals in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…Estimating the number of hospitalizations for these pathogens is challenging, and these different methodologic approaches have a major effect on the final estimate. For norovirus, despite differences in methodology and healthcare systems, our estimate (all modes of transmission) of the number of hospitalizations was in the same range as those estimated in North America ( 24 , 25 ) and in the Netherlands ( 26 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Estimating the number of hospitalizations for these pathogens is challenging, and these different methodologic approaches have a major effect on the final estimate. For norovirus, despite differences in methodology and healthcare systems, our estimate (all modes of transmission) of the number of hospitalizations was in the same range as those estimated in North America ( 24 , 25 ) and in the Netherlands ( 26 ).…”
Section: Discussionsupporting
confidence: 55%
“…and Salmonella spp. Data sources described in the literature to estimate the number of hospitalizations for norovirus, B. cereus , C. perfringens , and S. aureus infections include hospital discharge data and data from foodborne disease outbreaks ( 15 , 18 , 19 , 24 , 25 ). Estimating the number of hospitalizations for these pathogens is challenging, and these different methodologic approaches have a major effect on the final estimate.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, severe rotavirus infections are usually not fatal but may result in hospitalizations, generating important costs for society 2 . Before the arrival of rotavirus vaccines in Canada, there were on average 7,500 to 10,500 estimated hospitalizations for rotavirus gastroenteritis (RVGE) annually 3,4 . Rotavirus infections were responsible for up to 72% of AGE hospitalizations during winter months 5 …”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus is considered the most common cause of viral gastroenteritis and accounts for the highest percentage of patients presenting with a more severe clinical picture. This conclusion was reached by analyzing outpatients and hospitalized patients, and it has been found that the most common cause of hospitalization is rotavirus [3,[6][7][8][9][10][11]. However, studies that included only hospitalized patients have provided contradictory data about the severity of clinical picture of rotavirus and norovirus infections.…”
Section: Discussionmentioning
confidence: 99%